النون والميم في القرآن الكريم : دراسة صوتية حاسوبية (al-Nun wa al-mim fi al-Qur'an al-karim : dirasah sawtiyah hasubiyah) - Ahmed Mahmoud, Ahmed Ragheb (MEDIU, 2012)
Abstract: This study analyzes a range of phenomena relating to the alphabets Noon (ن) and Meem (م) in the Holy Quran by using sound evaluation, and examining the related variables that affect the sound in the recitation of the Quran. This study has been adopted on the basis of sound data that was characterized by inclusiveness and diversity, bringing Qur'an acoustic phenomena, and subjected it to a computing study in order to reach the results by trying to answer the study questions posed, and the requirements to descriptive lingual software adopted to monitor the phenomenon phonology of the Koran Quran. The study tried to take advantage of modern software in the study of Quranic sounds and the degree of usefulness and high accuracy in the analysis; in order to understand the Quranic sounds away from self-analysis, which results in either a confirmation of the provisions of traditional voice, or modify or add to the discovery of a number of provisions which was absent due to the old adoption on self and personal judgments.